A Case of Congenital Leukemia Cutis - Choi, Ji Hoon (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2009)
Congenital leukemia is a rare disease that develops from birth to 6 weeks of life. Leukemia cutis involves cutaneous infiltration by leukemic cells and is an unusual manifestation of leukemia, and has been documented in 25~30% of patients with congenital leukemia. The authors report a case of congenital leukemia cutis. A newborn male presented with widespread firm dusky red papules and nodules on almost his entire body surface. Skin biopsy specimens confirmed the presence of leukemic infiltrations, and bone marrow cytology was consistent with acute myeloid leukemia of the FAB M5 type.